Pacific Ocean Variability Influences the Time of Emergence of a Seasonally Ice‐Free Arctic Ocean - J. A. Screen; C. Deser (Geophysical Research Letters, 2019)
Abstract The Arctic Ocean is projected to become seasonally ice‐free before midcentury unless greenhouse gas emissions are rapidly reduced, but exactly when this could occur depends considerably on internal climate variability. Here we show that trajectories to an ice‐free Arctic are modulated by concomitant shifts in the Interdecadal Pacific Oscillation (IPO). Trajectories starting in the negative IPO phase become ice‐free 7 years sooner than those starting in the positive IPO phase. Trajectories starting in the negative IPO phase subsequently transition toward the positive IPO phase, on average, with an associated strengthening of the Aleutian Low, increased poleward energy transport, and faster sea‐ice loss. The observed IPO began to transition away from its negative phase in the past few years. If this shift continues, our results suggest increased likelihood of accelerated sea‐ice loss over the coming decades, and an increased risk of an ice‐free Arctic within the next 20–30 years.